Effects of grazing intensity and supplementation strategies on Tifton 85 production and on sheep performance - Silva, W. L. [UNESP]; Costa, J. P.R. [UNESP]; Caputti, G. P. [UNESP]; Lage Filho, N. M.; Ruggieri, A. C. [UNESP]; Reis, R. A. [UNESP] (Elsevier, 2019)
This study evaluated the structural and production characteristics of Tifton 85 (Cynodon spp.) pastures and the performance of lambs under different residual leaf area index (rLAI) and supplementation strategies in tropical conditions. Treatments were the factorial combination of 4- rLAI (0.8; 1.4; 2.0 and 2.6) and 2-supplementation strategies with four replicates in a randomized complete block design. The study was divided into two periods in southeastern Brazil: one in the rainy season and the other in the dry season. Lambs grazed under rotational stocking management and they grazed for 4 days in each pasture while pasture regrowth period was determined by the 95% light interception requirement. In the two evaluated periods the resting period and herbage accumulation decreased linearly and herbage allowance increased linearly with increasing rLAI. The chemical composition and digestibility were affected by rLAI only in the dry season. The dietary supplementation in the rainy season promoted increase of the gain per area but in the dry season the types of supplements did not promote changes in the animals performance. In the rainy season Tifton 85 pastures in rotational stocking can be managed with rLAI between 2.0 and 2.6 with approximately 18 days of regrowth period, and in the dry season with rLAI between 1.4 and 2.0 equivalent to the pasture regrowth period from 58–65 days.
Keywords: Dry season; Grazed stratum; Light interception; Rainy season; Residual LAI